MEDIA LITERACY EDUCATION FOR HIGH SCHOOL STUDENTS, ITS NECESSITY AND CHALLENGE - Trufi Murdiani (SOSIALITA, 2018)
Today, media and information grow very fast and needed by people from all age and background. It is no longer restricted to print and broadcast delivery, news and information are now accessible anywhere, at any time, to billions of people around the globe. Teenagers are now increasingly easy to get access to media and they need filter to get the good source of information from media. This goal can be reached with media literacy education. In the last 12 year, mainstream and new media in Lampung grows in rapid condition. Beside national media that distribute in Lampung, there are also local/provincial media as well as media, local and national TV, radio stations, news and information by internet and social media. Almost all high schools in Lampung Province especially in Bandarlampung City as the capital of its province, have already applied media literacy lesson. But the media literacy lessons are actually part of Bahasa Indonesia (Indonesian) course and given to students at the last level, for instance in SMAN 1 Bandarlampung where the media literacy focuses on information and communication technology (ICT) and this project was conducted.Keywords: